Reversible Hypopigmentation with Pazopanib - Srinivasa, B J; Lalkota, Bhanu Prakash; Chindar, Pramod S; Naik, Radheshyam (Indian Journal of Medical and Paediatric Oncology, 2018)
Tablet Pazopanib known to cause Hypo pigmentation and Hyperpigmentation as per various literature reports. We report here a case of reversible hypopigmentation with Pazopanib in a patient treated for spindle cell sarcoma. Patient did not have any clinical symptoms except for cosmetic significance.
Keywords: Pazopanib; hypopigmentation; reversible; tyrosine kinase inhibitor